Family Communication Patterns in Enhancing Children's Learning Motivation in Batang Kuis District, Deli Serdang Regency - Muhammad Farhan (Indonesian Journal of Communication and Social, 2025)
Family communication is the interaction that takes place within a family, namely the way a family member relates to other members, serving as a means to instill and develop values needed as life guidance. Learning is a process of behavioral change through education or, more specifically, through training procedures. From the traditional perspective, learning is an effort to acquire a certain amount of knowledge. The purpose of this study is to find out how family communication patterns enhance children’s learning motivation in Batang Kuis District, Deli Serdang Regency. This research applies a qualitative approach, carried out through interviews and documentation with a descriptive nature. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of the study indicate that the family communication pattern in this research tends to apply the Equality Pattern.